Dyslexia in primary school : an evaluation of the effectiveness of three models of special provision for pupils who have been assessed as having dyslexia - McPhillips, Thérèse (Trinity College (Dublin, Ireland). School of Education, 2007)
A number of recent initiatives in Ireland have begun to develop services for pupils who experience learning difficulties. However, reservations and uncertainty continue to surround the topic of dyslexia. Teachers are often unsure how to support the student with dyslexia in the classroom. Parents of children who have been assessed as having dyslexia will make every effort to be an advocate for the child in order to gain extra support. This extra support may take place in the child’s mainstream school from the learning support or resource teacher, or in a special setting such as enrolment in a reading unit or in a reading school.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin